Impact of tidal fluctuations on bacterial community structure in Wuyuan Bay: A comparative analysis of waters inside and outside the tidal barrage. - Dandan Xie; Chen Feng; Jiehua Hu; Huina Lin; Hong Luo; Qi Zhang; Haibin He (PLoS ONE)
The tidal barrage at Wuyuan Bay effectively mitigated the odor from the tidal flat during ebb tide, however, its effect on bacterial community structure in waters are still unclear. In this study, high-throughput sequencing was used to analyze the structure of the microbial community in waters inside and outside the tidal barrage during flood and ebb tides. Results showed bacterial diversity was higher in water outside the barrage during flood tide. The dominated species at phylum and genus levels were various in waters inside and outside the tidal barrage during flood and ebb tides. The water inside during ebb tide (E1) were dominated by two cyanobacterial genera, Cyanobium_PCC-6307 (42.90%) and Synechococcus_CC9902 (12.56%). The microbial function, such as porphyrin and chlorophyll metabolism and photosynthesis, were increased in E1. Norank_f__Nitriliruptoraceae was identified as differential microorganism in waters inside the barrage. Inorganic nitrogen and nonionic ammonia were significantly high in E1, and were negatively correlated with norank_f__Nitriliruptoraceae. These results suggest tidal barrage blocks water exchange, resulting in the accumulation of nutrients in Wuyuan Bay. Consequently, the environment became favorable for the growth of cyanobacteria, leading to the dominance of algae in the water inside the barrage and posing the risk of cyanobacterial bloom. Higher Nitriliruptoraceae inside the barrage might be a cue for the change of water quality.